Discover Manet & Eva Gonzalès - Herring, Sarah; Capron, Emma; Baker, Hannah; Higgitt, Catherine; Tomlinson, Hayley (National Gallery Global, 2022)
Edouard Manet (1832-1883) only ever had one formal pupil, Eva Gonzalès (1849-1883). The daughter of a prominent writer, she entered Manet's studio aged 19. He portrayed her the year they met and exhibited the ambitious full-length portrait at the Paris Salon of 1870, at which Gonzales also displayed her own work, for the first time, to positive reviews. The first in a new series of 'Discover' titles, in which a single work of art in the National Gallery's collection is reconsidered from a fresh perspective, this book reveals the extraordinary story behind Manet's portrait by examining it in the context of women's artistic practice in nineteenth-century Paris, Gonzales's development as a professional painter, and Manet's career in 1870. Combining new art historical research with engaging essays on women artists and their representation in visual culture, Discover Manet & Eva Gonzales provides a richly illustrated, in-depth study of Manet's portrait and offers a groundbreaking viewpoint on both artists. Exhibition: National Gallery, London, UK (21.10.2022 - 15.01.2023)
Rückseite Titelblatt: Published to accompany the exhibitions: "Eva Gonzalès is what Dublin needs", Hugh Lane Gallery, Dublin, 1 June-18 September 2022; "Discover Manet & Eva Gonzalès", The National Gallery, London, 21 October 2022-15 January 2023
Keywords: Gonzalès, Eva -- 1847-1883; Manet, Edouard -- 1832-1883; Geschichte 1870; Geschichte 1800-1900; Künstlerin; Bildnis; Bildnismalerei; Kunst; Paris; Ausstellungskatalog -- Hugh Lane Gallery -- 01.06.2022-18.09.2022 -- Dublin; Ausstellungskatalog -- The National Gallery -- 21.10.2022-15.01.2023 -- London; Aufsatzsammlung